Understanding Uterine Fibroids: Prevalence, Pathophysiology, and Management - Sadia, Haleema; Akram, Muhammad; Iftikhar, Momina; Umaru, Isaac John (Darul Yasin Al Sys, 2025)
The most common type of benign uterine tumors are uterine fibroids, sometimes referred to as leiomyomas or myomas. Clinical indicators include infertility, obstetric problems, mass symptoms, pelvic tumors, pelvic discomfort, and irregular bleeding. Because of their symptoms, more than 30% of women with leiomyomas might look for therapy. Modern surgical options are based on the operation, although the method of therapy is influenced by the patient's age and desire to avoid